Repetición de la prueba de intradermorreacción tuberculínica en bovinos naturalmente infectados y modifi caciones del pliegue anocaudal - Schneider, M. (2007)
The objective of the present work is to evaluate the repetition of the tuberculine skin test (TST) in cattle infected by Mycobacterium bovis and to determine the evolution of the size and consistency occurring in the caudal fold after the application of PPD. Fourteen naturally infected heifers were used to which the TST was repeated three times in folds in the caudal fold evaluating if the positive reaction remain as well as the physical characteristics of the caudal fold. 92,2% of the animals were positive in three repetitions and decrease in reaction size was observed, along with the successive repetitions. This endorses the national legislation that indicates not to repeat the test in positive animals.\n